Design of miniature waterjet machine - Arina, Mazelan (2016)
The waterjet machine has found wide acceptance and applications in the industries for the past few decades. It is proven to be sufficient for many cutting problems. The present work focuses on the design of miniature waterjet machine. The design of the waterjet machine was conducted based on various stages of product development process. All necessary systematic approaches in a product design based on VDI-guideline 2221 are presented in the present work. The main approaches begin with understanding the specification of the task in developing the miniature waterjet machine. It is then followed with evaluation of the conceptual design of the machine. Finally, the development of the final design of the miniature waterjet machine is presented.